Ellagic acid plays an important role in enhancing productive performance and alleviating oxidative stress, apoptosis in laying quail exposed to lead toxicity - Mutlu, Seda Iflazoglu; Seven, Ismail; Arkali, Gozde; Birben, Nurgul; Arslan, Aslihan Sur; Aksakal, Mesut; Seven, Pinar Tatli (Academic Press Inc Elsevier Science, 2021)
Lead (Pb) is one of the most toxic heavy metal environmental pollutants due to its widespread use of the industry and it is a harmful substance for human and animal health. This study was conducted to investigate the potential protective effects of ellagic acid (EA) on performance, egg quality, antioxidant parameters, and apoptotic pathway proteins in laying quails exposed to Pb toxicity. A total of 168 (15-week old) laying quails (Coturnix coturnix Japonica) were divided into 6 experimental groups (with similar initial average body weight). Birds were fed 1 of 6 diets for 8 weeks: 1 - Control (basal diet), 2 - Pb (basal diet + 100 mg/kg Pb), 3 - EA-300 (basal diet + 300 mg/kg EA), 4 - EA-500 (basal diet + 500 mg/kg EA), 5 - Pb + EA-300 (basal diet + 100 mg/kg Pb + 300 mg/kg EA), 6 - Pb + EA-500 (basal diet + 100 mg/kg Pb + 500 mg/kg EA). The results showed that adding 100 mg/kg of Pb to basal diet was adversely affected the performance parameters and, feed intake and egg production were significantly decreased by Pb supplementation (P 0.01). However, the EA supplementation to Pb groups improved the performance parameters. Compared with the Pb alone group, in Pb + EA-500 group increased egg production by 8.4%. There were no significant differences in the Haugh unit, albumen index, and yolk index among groups (P 0.05). Liver and kidney tissues of Pb group malondialdehyde (MDA) level increased (P < 0.001) and, GSH, GSH-Px, and CAT values decreased (P < 0.001) but, EA supplementation alleviated this condition (P < 0.001). The protein levels of caspase-3 and-9 were significantly increased in the Pb group compared to the control group, whereas EA supplementation alleviated the Pb-induced apoptosis by decreasing caspase-3 and-9 levels in the liver tissue (p < 0.001). In laying quails exposed to Pb toxicity, EA supplementation improves the performance parameters, enhances the antioxidant defense system, and suppresses apoptosis via regulates the expression of caspase-3 and-9. Thus, it was concluded that EA (especially 500 mg/kg) can ameliorate the toxic effects of Pb exposure in quails.
Keywords: Ellagic acid; Lead toxicity; Performance; Oxidative stress; Apoptosis; Quail